A measurement system for determining temperature, water potential and aeration of growth medium. - Heiskanen, Juha; Laitinen, Jukka (Silva Fennica, 1992)
A measurement system developed for the parallel and real-time measurement of temperature, matric potential and oxygen diffusion rate (ODR) of a growth medium was assessed. The system consisted of a portable computer, a datalogger, temperature sensors, tensiometers and an ODR-meter with Pt-sensors. For the measurements, proper sensor contact with the growth medium was needed. For matric potential measurement, appropriate shape and material of the tensiometer tips should be selected for different measurement purposes. The determination of oxygen diffusion rate is based on single, non-continuous measurements. The ODR-measurement required special care with the insertion and handling of the electrodes and selection of applied voltage. The ODR-measurement of a coarse peat medium was applicable only at matric potentials > -5 kPa. This measurement system was shown to be useful and suitable for accurate determination of thermal-, water- and aeration conditions of a growth medium under greenhouse conditions. The PDF includes an abstract in Finnish.